Business Development Strategy of PT XYZ as Distributor LPG 3 Kg in Cirebon - Mayrani Tika Mulyana; Syarief, Rizal; Anggraeni, Elisa (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Energy consumption such as oil and gas which still tends to be high makes business opportunities in the energy sector considered to have promising prospects. One of the energy products that are needed by the people of Indonesia is LPG (Liquefied Petroleum Gas). PT XYZ is a 3 kg subsidized LPG agent company that is classified as a highly regulated industry business, namely all of its business activities are supervised and regulated by the government and related agencies in this case through Pertamina. In industries that are tightly regulated, business competition between actors becomes very tight even though the barrier of entry is also high. To be able to enter this industry, business people must meet several requirements including requirements, capital, including the required LPG base permit. This strategy formulation at PT XYZ needs to be studied as a case of applying strategic management theory to a subsidized LPG distribution company. Data processing and data analysis methods in this study used descriptive analysis and three-stage analysis of strategy formulation. A tool for the three-stage analysis of strategy formulation using an internal factor matrix (IFE), external factor matrix (EFE), IE matrix, SWOT matrix and QSPM. Based on the IE matrix score, the position of cooperative is in first quadrant which means growing and building. The formulation of alternative strategies was based on IE matrix analysis and SWOT analysis to produce alternative development strategies. The strategy with the highest priority is based on the results of the Quantitative Strategic Planning Matrix, namely market penetration with a Sum Total Attractiveness (STAS) value of 6.084. Keywords: IE Matrix, LPG, SWOT, QSPM